Law Firm Internships and the Making of Future Lawyers: An Empirical Study in Singapore - Tan, Seow Hon (Institutional Knowledge at Singapore Management University, 2014)
This article examines the findings of an empirical study of law students from the Singapore Management University on their internship experiences at private law firms. As internships are frequently undertaken by law students, it is necessary for stakeholders to understand their impact on the values and ideals of law students in relation to the law and legal practice. This article seeks to increase the consciousness of law school educators, lawyers, and the professional bar about how law firm internships are contributing to the making of future lawyers, so as to facilitate the reflection by these parties as to their roles in shaping future lawyers.